Loss of Perp in T Cells Promotes Resistance to Apoptosis of T Helper 17 Cells and Exacerbates the Development of Experimental Autoimmune Encephalomyelitis in Mice - Zhou, Yan; Leng, Xiao; He, Yan; Li, Yan; Liu, Yuan; Liu, Yang; Zou, Qiang; Shi, Guixiu; Wang, Yantang (Frontiers in Immunology, 2018)
T helper 17 (Th17) cells are crucial for the pathogenesis of multiple sclerosis (MS) in humans and experimental autoimmune encephalomyelitis (EAE) in animals. High frequency of Th17 cells and low sensitivity to activation-induced cell death (AICD) are detected in MS patients. However, the mechanisms underlying apoptosis resistance of T cells remain unclear. Perp is an apoptosis-associated target of p53, and implicated in the development of cancers. Here, we show that loss of Perp in T cells does not affect Th1, Th17 or Treg cell differentiation, but does significantly increase the resistance of Perp-/- Th17 cells to AICD and anti-Fas in Lck-Cre×Perpﬂ/ﬂ mice by inhibiting the Caspase-dependent apoptotic pathway. Moreover, Lck-Cre×Perpﬂ/ﬂ mice exhibited earlier onset of EAE and severer spinal cord inflammation and demyelination, accompanied by increased levels of pro-inflammatory cytokines and enlarged population of Th17 cells. Therefore, Perp deletion promoted Th17 responses and exacerbated the development and severity of EAE.